2011
DOI: 10.1007/s00216-011-5376-6
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol profiling of microalgae strains for biofuel feedstock by liquid chromatography–high-resolution mass spectrometry

Abstract: Biofuels from photosynthetic microalgae are quickly gaining interest as a viable carbon-neutral energy source. Typically, characterization of algal feedstock involves breaking down triacylglycerols (TAG) and other intact lipids, followed by derivatization of the fatty acids to fatty acid methyl esters prior to analysis by gas chromatography (GC). However, knowledge of the intact lipid profile could offer significant advantages for discovery stage biofuel research such as the selection of an algal strain or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 38 publications
1
86
0
1
Order By: Relevance
“…This investigation has confirmed the potential of strains such as B. braunii for biodiesel production, but has also shown that under conditions of fast growth, other purportedly oleaginous strains have low FAME yields, suggesting minimal triacylglycerol accumulation. Lipid content values obtained from hexane extractions strongly suggested minimum neutral lipid content, a conclusion supported by LC-MS analysis [33]. In the future, our lab will be following the lead of other investigators [15,42] to directly quantify TAG accumulation to support these analyses.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This investigation has confirmed the potential of strains such as B. braunii for biodiesel production, but has also shown that under conditions of fast growth, other purportedly oleaginous strains have low FAME yields, suggesting minimal triacylglycerol accumulation. Lipid content values obtained from hexane extractions strongly suggested minimum neutral lipid content, a conclusion supported by LC-MS analysis [33]. In the future, our lab will be following the lead of other investigators [15,42] to directly quantify TAG accumulation to support these analyses.…”
Section: Discussionmentioning
confidence: 62%
“…5) show that this additional treatment did not extract all of the remaining fatty acids, indicating that manipulating Soxhlet extraction conditions will not likely result in the maximum yield of fatty acids in this case. It should be noted that these 'recalcitrant' fatty acids in B. braunii have been shown to be present at high abundance as C28:1/C18:1/C18:1 and C28:2/C18:1/C18:1 TAGs by previous liquid chromatography-mass spectrometry (LC-MS) studies [33]. These TAG may be difficult to extract due to their large molecular weight, though further analysis of intact TAG would be required to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…Freeze-dried whole algal biomass (WAB) was pulverized (to pass through a 0.5 mm screen) at 10,000 rpm using a laboratory ultra-centrifugal mill (Retsch model ZM200, Retsch GmbH., Haan, Germany) equipped with a pneumatic auto-feeder (Retsch model DR100) and stored at − 80°C. Lipidextracted biomass (LEB) was produced by solvent extraction of WAB on a Soxtec™ automated system (model 2050, FOSS North America, Eden Prairie, MN, USA) using HPLC-grade CHCl 3 :CH 3 OH (2:1 v/v) at 150°C for 82 min [22]. Residual solvents and moisture were eliminated by drying LEB in an oven 50°C for 24 h. Dried LEB from 60 pooled extractions per species were homogenized in a coffee grinder.…”
Section: Harvest and Sample Preparationmentioning
confidence: 99%
“…The emerging field of lipidomics has garnered much attention in the last few years due to the possibility for profiling large-scale lipid classes such as TGA, glycerolipids, among others [110,111]. This technology could also assist in the discovery of new feedstocks for biofuel production, which has been already successfully applied to microalgae in the selection of strains and/or optimization of biomass growth [112,113]. However, the use of lipidomics in higher plants has been limited to annotation of pathways [114][115][116] and response to environmental stresses [117], with no direct application for biofuels so far.…”
Section: Plant Metabolomicsmentioning
confidence: 99%